1977
DOI: 10.1210/jcem-45-5-996
|View full text |Cite
|
Sign up to set email alerts
|

The Prolactin Response to Neuroleptic Drugs. A Test of Dopaminergic Blockade: Neuroendocrine Studies in Normal Men

Abstract: The tonic inhibition of prolactin (PRL) secretion, which appears to be sustained mainly by hypothalamic dopaminergic activity, can be reliably disinhibited by neuroleptic, antidopaminergic drugs. The heuristic potential of this PRL response as a neuroendocrine model for studying hypothalamicpituitary regulation in man initiated the present intensive investigation.Nineteen normal young men were studied in a series of weekly experiments; at each session a single drug and dose, out of seven neuroleptic drugs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 16 publications
(22 reference statements)
3
40
0
Order By: Relevance
“…Metoclopramide is reported to specifically block hypothalamic and hypophyseal dopamine receptors (Jenner et al 1975;Yamauchi et al 1976), and has been shown to stimulate PRL secretion in man (McNeilly et al 1974;Delitala et al 1976;McCallum et al 1976;Judd et al 1976;Sowers et al 1976;Healy and Burger 1977;Langer et al 1977;Masala et al 1978). A simple oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Metoclopramide is reported to specifically block hypothalamic and hypophyseal dopamine receptors (Jenner et al 1975;Yamauchi et al 1976), and has been shown to stimulate PRL secretion in man (McNeilly et al 1974;Delitala et al 1976;McCallum et al 1976;Judd et al 1976;Sowers et al 1976;Healy and Burger 1977;Langer et al 1977;Masala et al 1978). A simple oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
“…As schizophrenics do not become tolerant to the antipsychotic effect of neuroleptics (17), the supposed lack of toler ance in the tuberoinfundibular system is inter preted to indicate the relevance of this dopa minergic system concerning the antipsychotic effects of neuroleptics (22,38,44). This hypo thesis is supported by the significant correlation between the potency to release Prl and the antipsychotic property of neuroleptics and other psychotropic drugs investigated in acute experiments (22,34). However, there is some evidence that the importance of the tubero infundibular pituitary axis with regard to the therapeutic actions of neuroleptics should not be overestimated: at least 3 neuroleptics do not fit into the mentioned correlation.…”
Section: Prolactinmentioning
confidence: 98%
“…46). During acute neuroleptic treatment, the plasma Prl level has been found to be significantly correlated with the serum levels of neuroleptics (31,51,54), but only within a narrow range as there is a maximal Prl response at low doses of neuroleptics, below the therapeutic range (22,34). Another significant correlation between the potency to release Prl and their antipsycho tic property has been reported (22,33).…”
Section: Introductionmentioning
confidence: 99%
“…Th is is based on evidence t hat plasma prola ctin conce nt ra t io ns are not eleva te d in pa t ien ts on clozapine t herapy, exce pt for an initi a l marginal incr ease th at is occasionally observed whi ch ra pid ly re t urns to bas e line with con t inue d treatm en t (28,29) . This is in con t rast to typi cal a n t ipsyc hot ics, whi ch elevat e plasma prolactin conce n t ra t ions throughout th erapy (30 ).…”
Section: Pharmacologymentioning
confidence: 81%